Evaluation of a CD13 and Integrin αvβ3 Dual-Receptor Targeted Tracer 68Ga-NGR-RGD for Ovarian Tumor Imaging: Comparison With 18F-FDG - Long, Yu; Shao, Fuqiang; Ji, Hao; Song, Xiangming; Lv, Xiaoying; Xia, Xiaotian; Liu, Qingyao; Zhang, Yongxue; Zeng, Dexing; Lan, Xiaoli; Gai, Yongkang (Frontiers in Oncology, 2022)
Ovarian cancer has the highest mortality rate of gynecologic malignancy. 18F-FDG positron emission tomography (PET) adds an important superiority over traditional anatomic imaging modalities in oncological imaging but has drawbacks including false negative results at the early stage of ovarian cancer, and false positives when inflammatory comorbidities are present. Aminopeptidase N (APN, also known as CD13) and integrin αvβ3 are two important targets overexpressed on tumor neo-vessels and frequently on ovarian cancerous cells. In this study, we used subcutaneous and metastatic models of ovarian cancer and muscular inflammation models to identify 68Ga-NGR-RGD, a heterodimeric tracer consisting of NGR and RGD peptides targeting CD13 and integrin αvβ3, respectively, and compared it with 18F-FDG. We found that 68Ga-NGR-RGD showed greater contrast in SKOV3 and ES-2 tumors than 18F-FDG. Low accumulation of 68Ga-NGR-RGD but avid uptake of 18F-FDG were observed in inflammatory muscle. In abdominal metastasis models, PET imaging with 68Ga-NGR-RGD allowed for rapid and clear delineation of both peritoneal and liver metastases (3-6 mm), whereas, 18F-FDG could not distinguish the metastasis lesions due to the relatively low metabolic activity in tumors and the interference of intestinal physiological 18F-FDG uptake. Due to the high tumor-targeting efficacy, low inflammatory uptake, and higher tumor-to-background ratios compared to that of 18F-FDG, 68Ga-NGR-RGD presents a promising imaging agent for diagnosis, staging, and follow-up of ovarian tumors.